IMPLEMENTATION OF THE TALKING STICK MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS 5 PPKN LEARNING - Cahya Putri Octaviana; Agung Setyawan; Mohamad Usman; Moh Rahbini (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This classroom action research was conducted with the aim of improving student learning outcomes in thematic learning PPKn content on Rights, Obligations and Responsibilities in the Community for Grade 5 SDN Banyuajuh 6, using the Talking Stick model during learning. This classroom action research was carried out for 2 cycles with the implementation of 1 cycle at one meeting. The stages of research include planning, implementation of action, observation and reflection. Data collection techniques in this study were tests (students' cognitive abilities) and non-tests (observation, documentation and field notes). While the data collection techniques using qualitative and quantitative. The results showed that there was an increase in student learning outcomes in each cycle. This can be seen from the results of the cognitive learning mastery of students in the Pre-Cycle of 55.28% increasing to 66.81% in Cycle I, then in Cycle II again increasing to 75.68%. In addition, as long as the Talking Stick Model is applied in learning, it is proven that there is an increase in student learning activities in a more positive direction. This can be seen from the results of observations of student activities which continued to increase from a score of 75 in the good and complete category during Cycle I, and during Cycle II the score increased to 85 in the good and complete category